Efecto de la aplicación de diferentes tipos de fermentación en la estabilidad de la grasa del cacao - Espinoza Loja, Nicole Estefanía; Gómez Ortega, Doménica Belén (My University, 2024)
The fermentation of cocoa almonds is a key process in determining their final quality, affecting physicochemical parameters such as pH, acidity, turbidity, and the oxidative stability of cocoa butter. In this study, the effect of three types of fermentation-spontaneous, alcoholic-acetic with molasses, and lactic with molasses and Lactiplantibacillus plantarum was evaluated to identify the most efficient treatment for obtaining butter with greater stability and lower susceptibility to oxidation. Fine-aroma cocoa almonds were subjected to fermentation under controlled conditions, followed by drying and roasting. The butter extraction was carried out using a mechanical extruder, and physicochemical analyses were performed to evaluate changes in its composition. Soluble solids content, pH, acidity, turbidity, and oxidation levels were determined. Turbidity measurements were taken using a UV-Visible spectrophotometer at 340 nm, while oxidation was assessed after a controlled temperature storage period. The results showed that fermentation directly influences cocoa butter quality. Spontaneous fermentation resulted in higher turbidity and lower extractable fat content. In contrast, alcoholic-acetic fermentation and lactic fermentation with L. plantarum led to a reduction in turbidity and an increase in the amount of extracted butter, suggesting that these processes improve yield efficiency and final product purity. Statistical analysis (ANOVA) revealed significant differences between treatments regarding the oxidative stability of cocoa butter (p = 0.00698), indicating that the type of fermentation affects oxidation resistance. The coefficient of determination (R² = 0.5212) showed that approximately 52.12% of the variability in oxidation is due to the type of fermentation applied. These results indicate that fermentation can be used as a tool to enhance the stability of cocoa butter, optimizing its quality and commercial potential. This study provides valuable information on the influence of the fermentation process on cocoa butter and its oxidative stability. The findings may contribute to the development of controlled fermentation methodologies that promote the production of high-quality cocoa, with applications in both the food and cosmetic industries. Additionally, these results could be useful for optimizing fermentation processes at an industrial level and improving the competitiveness of Ecuadorian cocoa in the international market.
La fermentación de las almendras de cacao es un proceso clave en la determinación de su calidad final, afectando parámetros fisicoquímicos como el pH, la acidez, la turbidez y la estabilidad oxidativa de la manteca de cacao. En este estudio, se evaluó el efecto de tres tipos de fermentación: espontánea, alcohólica-acética y láctica, con el fin de identificar el tratamiento más eficiente en la obtención de una manteca con mayor estabilidad y menor susceptibilidad a la oxidación. Las almendras de cacao fino de aroma fueron sometidas a fermentación bajo condiciones controladas, seguidas de secado y tostado. La extracción de la manteca se llevó a cabo mediante un extrusor mecánico, y se realizaron análisis fisicoquímicos para evaluar los cambios en su composición. Se determinó el contenido de sólidos solubles, pH, acidez, turbidez y grado de oxidación. Para la medición de la turbidez se utilizó un espectrofotómetro UV-Visible a 340 nm, mientras que la oxidación se midió tras un periodo de almacenamiento a temperatura controlada. Los resultados mostraron que la fermentación influye directamente en la calidad de la manteca. Se observó que la fermentación espontánea presentó mayor turbidez y menor cantidad extraíble de grasa. En contraste, la fermentación alcohólica-acética y la láctica con L. plantarum mostraron una reducción en la turbidez y un aumento en la cantidad de manteca extraída, lo que sugiere que estos procesos mejoran la eficiencia del rendimiento y la pureza del producto final. El análisis estadístico ANOVA reveló diferencias significativas entre los tratamientos en cuanto a la estabilidad oxidativa de la manteca (p = 0.00698), indicando que el tipo de fermentación afecta la resistencia a la oxidación. El coeficiente de determinación (R² = 0.5212) mostró que aproximadamente el 52.12% de la variabilidad en la oxidación se debe al tipo de fermentación aplicada. Estos resultados evidencian que la fermentación puede ser utilizada como una herramienta para mejorar la estabilidad de la manteca de cacao, optimizando su calidad y potencial comercial. El estudio aporta información valiosa sobre la influencia del proceso fermentativo en la manteca de cacao y su estabilidad oxidativa. Los hallazgos pueden contribuir al desarrollo de metodologías de fermentación controladas que favorezcan la producción de cacao de alta calidad, con aplicaciones tanto en la industria alimentaria como en la cosmética. Además, estos resultados pueden ser útiles para optimizar procesos de fermentación a nivel industrial y mejorar la competitividad del cacao ecuatoriano en el mercado internacional.
Keywords: FERMENTACIÓN; MANTECA DE CACAO; OXIDACIÓN; TURBIDEZ.